PENGARUH MODEL PROBLEM BASED LEARNING (PBL) BERBANTUAN MEDIA DIORAMA DALAM MENINGKATKAN HASIL BELAJAR SISWA KELAS III SD - Amitha Salsabilla; Deki Wibowo; Yoga Awalludin Nugraha (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aimed to analyze the effect of implementing the Problem Based Learning (PBL) model assisted by diorama media on third-grade students’ science (IPAS) learning outcomes in the topic of metamorphosis. The research employed a quantitative approach using a Pre-Experimental design (One Group Pretest–Posttest), involving 30 third-grade students of SDN 2 Dorang as the research subjects. Data were collected through validated pretest and posttest instruments that had undergone validity, reliability, item difficulty, and discrimination power testing. The data were analyzed using normality testing and the Paired Sample t-test. The results indicated an increase in the mean score from 53.23 in the pretest to 85.63 in the posttest. The Shapiro–Wilk normality test showed significance values of 0.129 (pretest) and 0.124 (posttest), indicating that the data were normally distributed. Furthermore, the Paired Sample t-test revealed a significance value of 0.000 < 0.05 with a t-value of -17.652 (df = 29), demonstrating a statistically significant difference between students’ learning outcomes before and after the treatment. Therefore, it can be concluded that the implementation of the PBL model assisted by diorama media has a significant and effective impact on improving elementary students’ science learning outcomes, particularly on the topic of metamorphosis.